Total Phenol, Antioxidant and Antibacterial Activity of the Essential Oil and Extracts of Ferulago angulata ssp. angulata - N Hosseini; M Akbari; R Ghafarzadegan; S Changizi Ashtiyani; R Shahmohammadi (Institue of Medicinal Plants, ACECR, 2012)
Background: In recent years, plants natural products have gained considerable attention as natural preservers for use in different industries. Due to their free radical scavenging activities, phenolic compounds can prevent a wide range of diseases such as cancers and cardiovascular and neurodegenerative diseases. For a long time, different Ferulago species have been in use as medicinal plants worldwide.   Objective: The aim of this research was to investigate total phenolics and the antioxidant and antibacterial activities of essential oil and different extracts from F. angulata growing wild in Iran.   Methods: Antioxidant activity of our samples was examined by DPPH assay and their phenolic content was determined using the Folin - Ciocalteau method. Moreover, their inhibitory effects against five gram-negative and gram-positive bacteria including Shigella boidii, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Enterococcus faecalis were tested by using the disk diffusion method.   Results: Ethyl acetate fraction and methanol extract contained the highest levels of phenolic compounds (229.2 and 202.9 µg/mg galic acid) in this study. Also, essential oil of this plant exhibited low free radical scavenging activity (IC50= 36129.43µg/ml). On the other hand, ethyl acetate and aqueous fractions had the highest antioxidant activity (IC50 values of 20.153 and 28.28 µg/ml, respectively). Finally, studied samples had no significant antibacterial activities against tested organisms.  Conclusion: The essential oil of this plant can be used as a flavoring agent while extracts prepared from it have the potential to be used as natural antioxidants in relevant industries.